Pusat Pembangkit Listrik Hybrid dan Industri Penghasil Energi Alternatif yang Terbarukan Sebagai Bagian Dari Sumber Daya Alam Masyarakat di Desa Kemujan Karimun Jawa - Wan Lubnayya Nabigha (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2026)
The project redefines the conventional powerplant from a centralized and isolated industrial facility into a distributed coexistent energy network integrated with the island’s ecology and daily life. Responding to different environmental potentials across the island, solar, wind, and diesel backup systems are placed in context-driven locations where energy infrastructure also supports public, productive, and ecological activities. These decentralized modules are interconnected through a central hub that acts as a metabolic machine for monitoring, storage, and system integration, while the diesel generator gradually shifts into emergency-only infrastructure. Through this approach, the hybrid powerplant becomes not only a system for generating electricity, but an adaptive architectural landscape where energy, environment, and society coexist.